Improving clinical care outcomes for Canadian seniors: findings of a pilot study evaluating an applied simulated and integrated learning approach (ASILA) for home care workers. Issue 10 (3rd October 2019) - Boscart, Veronique M.; Crutchlow, Lauren; Taucar, Linda Sheiban; Schelling, Sandra; Fung, Elliott; Betini, Raquel S. D.; Heckman, George; Hirdes, John
ABSTRACT: Home care workers deliver care services to community-dwelling seniors across Canada, but home care workers' variable education and unfamiliarity with assessment data systems can impede client-centered care. This pilot study therefore examined the effectiveness and feasibility of five educational modules on geriatric care, developed with a pedagogical framework used to educate and empower home care workers, in improving care beliefs and attitudes, care provision challenges, and satisfaction with modules. Online versions of modules, which used clinical scenarios and interRAI home care to guide care procedures, were developed. Participants' care beliefs and attitudes, care provision challenges, and satisfaction were measured before and after module delivery using non-standardized questionnaires. Quantitative data was analyzed using descriptive and inferential statistics, whereas qualitative data was analyzed using content analyses. Although most participants already completed training at least once a year (52.9%) and believed they were knowledgeable of clients' needs (85.3%), modules showed significant improvement on 46.4% of participants' care attitudes and beliefs. Participants thought that modules focused on important educational topics for home care workers (94.3%) and provided useful information (n=19). The majority (79.5%) of participants were satisfied with modules and 68.6% could see them being completed online in the future. Educational modules, focusing on integrated and applied geriatric care interventions significantly improved home care workers' gerontological knowledge and skills. Accessible and low-cost continuing education on geriatric home care hereby presents as an effective and acceptable way of building home care workers' care capacity.